Perawatan Paliatif terhadap Kualitas Hidup Pasien Covid-19 - Irawan, Ella Wahyu; Sukendra, Dyah Mahendrasari (Center for Public Health Nutrition Studies, Universitas Negeri Semarang, Indonesia, 2023)
Background: Palliative care is patient and family centered care with the goal of optimizing quality of life by anticipating, preventing, and treating suffering, when “curative” therapy may be futile. To improve the quality of life of Covid-19 patients, a number of treatments are needed, including palliative care for Covid-19 patients. This study aims to determine the relationship between palliative care and the quality of life of Covid-19 patients. Methods: This type of research is analytic observational with a cross sectional design. The sample is set at 75 respondents using the Convenience Sampling technique. The instruments used are questionnaire guidelines, and medical records. Data were analyzed using chi-square test by calculating odds ratio (OR), 95% significance level, and logistic regression test to determine the most dominant variable. Results: The results showed that anxiety disorders (p-value=0.01; OR=4.37; 95% CI=1.42-13.47), feelings of depression (p-value=0.02; OR=3.32; 95% CI=1, 26-8.72), feeling depressed (p-value=0.01; OR=4.18; 95% CI=1.43- 12.17), health status (p-value= 0.04; OR=3; 95% CI=1.15-7.81), social support (p-value=<0.01; OR=6.18; 95% CI=2.23-17.12 ), and life satisfaction (p-value=<0.01; OR=8.08; 95% CI=2.70-23.43) was associated with the quality of life of Covid-19 patients. Conclusion: The determinant most related to the quality of life of Covid-19 patients is life satisfaction.